2015
DOI: 10.17765/2176-9168.2015v8n3p585-600
|View full text |Cite
|
Sign up to set email alerts
|

Percepção dos Consumidores de Soja e Derivados na Cidade de Júlio de Castilhos (RS) - Brasil

Abstract: RESUMO:O Brasil ocupa o segundo lugar no ranking mundial de produção de soja desde 2003, sendo que o complexo derivado deste grão tem expressiva contribuição econômica no país. O movimento dos consumidores no intuito de ter uma alimentação mais saudável quanto à qualidade e aspectos nutricionais dos alimentos impulsionou a indústria para o desenvolvimento de uma maior variedade de produtos e, neste contexto, a soja tem se mostrado como uma importante fonte nutritiva. Este estudo objetivou avaliar a percepção d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…Consumer's acceptance of soy-based functional foods is not well known [10]. Despite the fact that Brazil is a major global producer of soybean, studies found that the consumption of soy and derivatives by Brazilians is low, corroborating the data found in this investigation [11,12].…”
Section: Discussionsupporting
confidence: 84%
“…Consumer's acceptance of soy-based functional foods is not well known [10]. Despite the fact that Brazil is a major global producer of soybean, studies found that the consumption of soy and derivatives by Brazilians is low, corroborating the data found in this investigation [11,12].…”
Section: Discussionsupporting
confidence: 84%
“…This was due to favorable environmental conditions for cultivating soybeans, corn (Zea mays) and wheat (Triticum aestivum) that, when integrated together, support soil conservation practices and increase nitrogen in the soil, resulting in better soil fertility (Caldarelli, Câmara, & Sereia, 2009;Andrade et al, 2016). In Brazil, soybeans are integrated into practically every production unit, provide additional income for farmers, are processed and sold domestically or exported internationally, and generate more than a million direct and indirect jobs throughout the country (Dotto et al, 2015;Ribeiro et al, 2017).…”
Section: Introductionmentioning
confidence: 99%